Foreign ownership, domestic ownership and capital structure: special reference to manufacturing companies quoted on Colombo Stock Exchange in Sri Lanka. - Sivathaasan, N. (European Journal of Business and Management, 2013)
Firm ownership plays a vital role in emerging economies and has become important to influence decisionmaking process. The primary aim of this paper is to investigate the impact of foreign and domestic ownerships on capital structure decision among quoted manufacturing firms in Sri Lanka during 2009 to 2011.The studyadopts correlation and regression models to measure the relationship between ownership and capital structureand to test the operational hypotheses. The results revealed that foreign ownership has a strong positiveassociation with leverage (r =.569), whereas leverage is negatively correlated with domestic ownership (r = -.544).According to regression model, ownership structure has an impact on leverage at the rate of 36 %(R2=0.36), which is insignificant at 0.05 levels. This study would hopefully benefit to the academicians,researchers, policy makers, and practitioners of Sri Lanka as well as other countries.
Keywords: Foreign Ownership; Domestic ownership; Capital Structure; Colombo Stock Exchange